Assessment of the pharmacology and tolerability of PF-04457845, an irreversible inhibitor of fatty acid amide hydrolase-1, in healthy subjects - Li, Gai Ling (Blackwell Science Inc, 2012)
AIMS: To evaluate the pharmacology and tolerability of PF-04457845, an orally available fatty acid amide hydrolase-1 (FAAH1) inhibitor, in healthy subjects. METHODS: Double-blind, randomized, placebo-controlled single and multiple rising dose studies and an open-label, randomized, food effect study were conducted. Plasma and urine PF-04457845 concentrations, plasma fatty acid amide concentrations and FAAH1 activity in human leucocytes were measured. Tolerability, including effects on cognitive function, were assessed. RESULTS: PF-04457845 was rapidly absorbed (median t(max) 0.5–1.2 h). Exposure increased supraproportionally to dose from 0.1 to 10 mg and proportionally between 10 and 40 mg single doses. The pharmacokinetics appeared dose proportional following 14 days once daily dosing between 0.5 and 8 mg. Steady-state was achieved by day 7. Less than 0.1% of the dose was excreted in urine. Food had no effect on PF-04457845 pharmacokinetics. FAAH1 activity was almost completely inhibited (>97%) following doses of at least 0.3 mg (single dose) and 0.5 mg once daily (multiple dose) PF-04457845. Mean fatty acid amide concentrations increased (3.5- to 10-fold) to a plateau and then were maintained following PF-04457845. FAAH1 activity and fatty acid amide concentrations returned to baseline within 2 weeks following cessation of dosing at doses up to 4 mg. There was no evidence of effects of PF-04457845 on cognitive function. PF-04457845, at doses up to 40 mg single dose and 8 mg once daily for 14 days, was well tolerated. CONCLUSIONS: PF-04457845 was well tolerated at doses exceeding those required for maximal inhibition of FAAH1 activity and elevation of fatty acid amides.